(untitled) (International Journal of Food and Nutritional Sciences, 2023)
MGNREGS is the most significant scheme to uplift the overall quality of life of rural households. One of the major objectives of the scheme is to improve the income levels of the rural poor and thereby provide livelihood security in rural areas by guaranteeing 100 days of wage employment in a financial year to every registered household. Study revealed that MGNREGA overall has been successful in providing works to the beneficiaries. This scheme facilitates infrastructural development at village level. Moreover, the scheme has been able to reduce the rural urban migration by making employment opportunities available at the place of residence. Overall, results showed a satisfactory (positive) impact of MGNREGA on the rural livelihoods. However, there is need of reforms in this scheme in order to make the working of MGNREGA much better. During the study, it was found that the beneficiaries are not satisfied with the existing wage rate they received for work done under MGNREGA. Issue of delay payments need to be rectified. Wastage of funds should be checked. To make the Act more effective for securing the desired objectives of rural poverty eradication and livelihood security, there is an urgent need to ensure citizen participation in all stages of the implementation process.